THREE-DIMENSIONAL RESISTIVITY MODEL FOR GROUND WATER EXPLORATION IN VOLCANIC ZONE OF TIDAR PLETEAU, MALANG, EAST JAVA - Irwan, Irwan; Ilham; Adi Susilo (Universitas Mataram, 2020)
Geoelectrical resistivity method is popular technique for subsurface mapping of groundwater, mining exploration, and structural geology. For case study in Tidar Plateau which characterized by hard rock of volcanic breccia, lava, tuff, and conglomerate, the groundwater system occurs only by the secondary porosity (faulting, facturing, and weathering). Therefore it becomes difficult task for determine position of good well site in Tidar Plateau. Geoelectrical technique by Schlumberger configuration was choosen to investigated the ground water system in this area. Total 5 Vertical Electrical Sounding (VES) acqusition point (400 m length measurement; spacing 10 m) for data measurement with coverage area about 400 x 400 m2. For data processing was used IP2Win, Progress3, and RockWork 16. The data processing results showed high accuration with avarage Root Mean Square (RMS) error about 0.3 – 8.3 %. According to resistivity results, the study area has resistivity between 0.3– 2.5x104 . The rocks which have resistivity between 0.3 – 12.52 interpreted as sandy-clay; 12.52 – 50 interpreted as wet sandstone (aquifer); 129 – 178 interpreted as conglomerat; 700 – 1300 interpreted as tuff, sand, and dry gravel; 2600 – 2.5x104 interpreted as volcanic breccia. This geoelectrical results has succesful finding the fresh water at VES 5 after drilled at depth 100 m at wet sandstone formation. To findout distrubution of aquifer layer, a three-dimensional (3D) resistivity model was developed. The 3D resistivity model shows the aquifer layer image look the dome-like structure and image the fracture regions which becomes the pathway of groundwater system.